Pendidikan Antikorupsi melalui Budaya Sekolah Berbasis Nilai-nilai Keislaman - Harmanto Harmanto (Islamica: Jurnal Studi Keislaman, 2012)
Corruption has become a kind of endemic in a country like Indonesia. It becomes our serious challenge therefore to deal with it properly and appropriately. This paper argues first and foremost that combating corruption through law enforcement is not enough. It proposes instead, that preventing corruption can only be effective and affective through education. By education we mean that which sharpens and softens the mindset, attitudes, and behavior of the educated. Our schools have hitherto been focusing on the cognitive aspect of education only ignoring in that process its spiritual and affective aspects. What is needed?this paper further argues?is value inculcation in the mind and heart of the students in such a way that when they grow up they can look after themselves as far as avoiding vices is concerned. Value inculcation in turn can only work when a religious education and instruction is involved. Hence, good education is what which incorporates religious teaching and doctrine into the system of education. It is to this point that this paper is destined.